Open educational resources: inquiring into author use and reuse. (10th September 2008) - Petrides, Lisa; Nguyen, Lilly; Jimes, Cynthia; Karaglani, Anastasia
For teachers and learners, the proliferation of Open Educational Resources (OER) in combination with advances in information technologies has meant centralised access to materials and the possibility of creating, using, and reusing OER globally, collaboratively, and across multiple disciplines. Through an examination of a community of author users of the OER portal Connexions, this article explores individual and group authorship, OER use and reuse and the factors contributing to and hindering these practices. As such, the paper sheds light on how OER can be sustained and continuously improved, with an emphasis on the use and reuse of dynamic, relevant, and high quality materials over time.